Співробітництво ЄС та МЕРКОСУР як приклад для подальшої інтеграції України - Олійник, Юлія (Видавництво Львівської політехніки, 2015)
Враховуючи, що найголовнішою складовою економічного та політичного розвитку будь-якої держави, що визначає її майбутнє, та констатуючи, що сьогодні консолідація держав охопила майже усі континенти, а більшість інтеграційних об’єднань носить не лише економічний, але й політичний характер, в роботі досліджено інтеграційне об’єднання Південної Америки, а саме – МЕРКОСУР та його співробітництво з Європейським Союзом. Досвід співпраці двох інтеграційних проектів є надзвичайно актуальним і для України, яка сьогодні продовжує інтеграційний поступ до євроспільноти. The author investigates the activities of such organisations as Mercosur and the EU in order to ascertain the effectiveness of the most powerful intergovernmental unions that include most countries of two different continents and each of them claims to be a leader in its part of the world. These integration associations not only implement a common economic policy but they have also achieved significant success in common political and social spheres. The EU–Mercosur relations are constantly developing towards strengthening their cooperation and establishing closer economic ties such as the Free Trade Agreement (FTA). Therefore, the investigation and comparison of the various aspects of the integration processes in Europe and South America are considered to be necessary as the results of such research can serve as an analytical basis for establishing further relations between Ukraine and the European Union today. The history of Mercosur as well as the development of the European Union began with the economic union of the countries. The market of the «Southern Cone» in comparison with the EU is a rather new organisation but for twenty-three years of its existence it has already proved its effectiveness and achieved its first results. The author points out that at the current stage of its development the EU is not a purely economic organisation but it has already become a political union of the member countries. The authorities of this Latin American association intend to transform it into a closer alliance following the EU example. The author describes Mercosur and the EU as the international organisations that consolidated the states into one common area being the consolidating authorities of these countries in Europe and South America. The study of the integration processes on two different continents can help to develop the appropriate foreign policy direction for our country.
The cooperation between the EU and Mercosur as the example for the further integration of Ukraine
Keywords: МЕРКОСУР; ЄС; інтеграція; євроінтеграція; Mercosur; the EU; integration; eurointegration